Nonfunctional extradural thoracic spine paraganglioma in a pediatric patient: a case report - Alshaya, Weal (J Surg Case Rep, 2020)
Paraganglioma in the spine remains a rare occurrence that is mostly benign and commonly associated with other inherited symptoms. Presentation in the pediatric population is rare with a high risk of recurrence. This case reports an unusual presentation of a slowly progressing nonfunctional thoracic paraganglioma in a 6-year-old female child that presented with mass-related symptoms sparing the spinal canal. Tumor recurred after initial video-assisted thoracoscopic surgery excision with significant involvement of the thoracic spinal canal. Patient underwent a second surgery utilizing a posterior approach and laminectomies. Succinate dehydrogenase-B gene association was confirmed through molecular testing afterward. Such tumors can be malignant with 7% present with distant metastasis. Image-based differentiation of malignant tumors remains difficult, adding to the urgency in diagnosing these tumors. Furthermore, the unlikely age presentation compounds to the challenges of the diagnostic process.x The patient remains tumor free 12 months postoperatively.